Analysis of Furniture Product Quality Control with Statistical Quality Control Methods and Failure Mode and Effect Analysis - Ghufron, Muhammad Zhaki; Aryanny, Enny; Islami, Mega Cattleya Prameswari Annissaa (Journal La Multiapp, 2024)
PT. Tjakrindo Mas is a manufacturing company based in Indonesia that supports the government, industrial, public, and private sectors. Established in 1984, the company produces home furniture made from various types of wood. During the period from December 2023 to May 2024, the company faced production issues with its furniture products. According to production scheduling data, the furniture production intensity was high, operating 5 days a week. During this period, the highest production rate was for the 2 Door Glass Wardrobe, totaling 5,638 units. However, despite the high production volume, the defect rate for the 2 Door Glass Wardrobe was also high, with 498 defective units, representing a defect rate of 8.83%, which exceeds the company's tolerance standard. The objective of this study is to assess the quality of the Glass Wardrobe product at PT. Tjakrindo Mas and to propose improvements to enhance the product quality. Observations identified that the highest Risk Priority Number (RPN) was associated with the close side rail rupture defect, caused by the operator not being careful when installing the close side rail to the cabinet body, and the work methods used not in accordance with the Standard Operating Procedure (SOP). Recommendations for quality control proposals based on the high RPN value of FMEA Close Side Rail Rupture is to provide supervision and guidance to workers, and Provide briefing to operators about methods that are in accordance with the standard operating procedures (SOP) used by the company.